Post-Divorce Child Support Obligations as Ex Lege Obligations and Its Implications for Legal Certainty in the Perspective of Civil Procedure Law - Zahra Aolia; Gusti Yosi Andri (Ann Publisher, 2026)
Background. The obligation to support children after divorce has been normatively regulated in laws and regulations, but in judicial practice it is often not stated in the decision, thus creating a gap between material law and procedural law in ensuring legal certainty in fulfilling children's rights. Aims. This study aims to analyze whether the obligation to support a child born directly under the law (ex lege) or depends on a court decision, as well as assess the harmony between material law and procedural law. Result. The results of the study show that the obligation of child support is juridically an ex lege obligation that is born directly from the law and is imperative and binding without the need for the appointment of a judge. However, in judicial practice, these obligations are not always stated in the judgment because the judge is bound by the passive and ultra petita principles that limit the scope of the decision to the petitum submitted by the parties. Conclusion. This condition shows a disharmony between material law and procedural law, which has an impact on the lack of optimal legal certainty in fulfilling children's rights after divorce. Implementation. As a result, maintenance obligations often do not have executory force if they are not applied, so their implementation depends on the judge's decision.